spa typing and antimicrobial resistance of Staphylococcus aureus from healthy humans, pigs and dogs in Tanzania - Katakweba, Abdul Sekemani; Muhairwa, Amandus Pachificus; Espinosa-Gongora, Carmen; Guardabassi, Luca; Mtambo, Madundo M A; Olsen, John Elmerdahl (The Journal of Infection in Developing Countries, 2016)
Introduction: Staphylococcus aureus is an opportunistic pathogen causing infections in humans and animals. Here we report for the first time the prevalence of nasal carriage, spa typing and antimicrobial resistance of S. aureus in a Tanzanian livestock community. Methodology: Nasal swabs were taken from 100 humans, 100 pigs and 100 dogs in Morogoro Municipal. Each swab was enriched in Mueller Hinton broth with 6.5% NaCl and subcultured on chromogenic agar for S. aureus detection. Presumptive S. aureus colonies were confirmed to the species level by nuc PCR and analysed by spa typing. Antimicrobial susceptibility patterns were determined by disc diffusion method. Results: S. aureus was isolated from 22 % of humans, 4 % of pigs and 11 % of dogs. A total of 21 spa types were identified: 13, 7 and 1 in human, dogs, and pigs, respectively. Three spa types (t314, t223 and t084) were shared between humans and dogs. A novel spa type (t10779) was identified in an isolate recovered from a colonized human. Antimicrobials tested revealed resistance to ampicillin in all isolates, moderate resistances to other antimicrobials with tetracycline resistance being the most frequent. Conclusion: S. aureus carrier frequencies in dogs and humans were within the expected range and low in pigs. The S. aureus spa types circulating in the community were generally not shared by different hosts and majority of types belonged to known clones. Besides ampicillin resistance, moderate levels of antimicrobial resistance were observed irrespective of the host species from which the strains were isolated.